(untitled) (Research, Society and Development, 2019)
Education in general is witnessing a moment of search for change, in the teaching of chemistry is no different, these changes usually occur in a curriculum reformulation where it is contemplated an improvement in content and teacher training courses, with a consequent improvement in teaching-learning process. This article aims to suggest the application of an annual discipline plan where each subject taught in theory will be applied a related practical class. The purpose of this article is to discuss the importance of using practical Chemistry classes in the laboratory to assist in the teaching-learning process of high school students. Show that the realization of experiments helps to bring the chemistry seen in the classroom to the students’ everyday life, thus making the classes more dynamic. The teaching of chemistry should develop in students the ability to understand the chemical phenomena present in their day to day.